Accounting Factors, Non-Accounting Factors, and Net Initial Return - Dhian Nurul Hidayati; Dedik Nur Triyanto (Journal of Accounting Auditing and Business, 2020)
The research aims to analyze accounting and non-accounting factors that influence the level of Net Initial Return (NIR). Accounting factors contain Return on Asset (ROA), Debt to Equity Ratio (DER), and Firm Size. Non-accounting factors contain Firm Age, Offering, and Underwriter Reputation. Furthermore, the research has the purpose of finding any simultaneous and partial influence. The research is using a quantitative method. The population is 149 companies that have made any Initial Public Offering (IPO) on the Indonesia Stock Exchange in the 2014-2018 period. The sample-based on purposive sampling results which are 95 companies. Multiple linear regression analysis was applied in this research using EViews 10. Simultaneously, the result indicates that ROA, DER, Firm Size, Firm Age, Offering, Underwriter Reputation have a significant influence on NIR. However, partially, the results showed that only ROA and Underwriter Reputation have a negative and significant effect on NIR. Meanwhile, DER, Firm Size, Firm Age, and Offering do not have a substantial effect on NIR.